Earth‐Abundant Transition‐Metal‐Based Electrocatalysts for Water Electrolysis to Produce Renewable Hydrogen. Issue 69 (21st November 2018) - Li, Ailong; Sun, Yimeng; Yao, Tingting; Han, Hongxian
Abstract: Fundamentals of water electrolysis, and recent research progress and trends in the development of earth‐abundant first‐row transition‐metal (Mn, Fe, Co, Ni, Cu)‐based oxygen evolution reaction (OER) and hydrogen evolution (HER) electrocatalysts working in acidic, alkaline, or neutral conditions are reviewed. The HER catalysts include mainly metal chalcogenides, metal phosphides, metal nitrides, and metal carbides. As for the OER catalysts, the basic principles of the OER catalysts in alkaline, acidic, and neutral media are introduced, followed by the review and discussion of the Ni, Co, Fe, Mn, and perovskite‐type OER catalysts developed so far. The different design principles of the OER catalysts in photoelectrocatalysis and photocatalysis systems are also presented. Finally, the future research directions of electrocatalysts for water splitting, and coupling of photovoltaic (PV) panel with a water electrolyzer, so called PV‐E, are given as perspectives. Abstract : Fundamentals of water electrolysis, and recent research progress and trends in the development of earth‐abundant first‐row transition‐metal (Mn, Fe, Co, Ni, Cu)‐based oxygen evolution reaction (OER) and hydrogen evolution (HER) electrocatalysts working in acidic, alkaline, or neutral conditions are reviewed.